SCIENTIFIC AND THEORETICAL BASIS FOR DEVELOPING INNOVATIVE COMPETENCE OF PRESCHOOL STUDENTS IN HIGHER EDUCATION - Aziza Kobilova Tursunovna (Scholar Express Journals, 2023)
It is important to improve the scientific and methodological foundations of vocational education in fulfilling the growing requirements for creative individuals capable of successfully solving the current problems of science, economics, manufacturing and the education system
Keywords: Competence; Innovation; Preschool; Cognitive